(untitled) (Hoboken, N.J., 2008)
Written by a multidisciplinary group of soil and environmental scientists, Biophysico-Chemical Processes of Heavy Metals and Metalloids in Soil Environments provides the scientific community with a critical qualitative and quantitative review of the fundamentals of the processes of pollutants in soil environments. The book covers pollutants' speciation, mobility, bioavailability and toxicity, and impacts on development of innovative restoration strategies. In addition, the development of innovative remediation strategies for polluted soils is covered.
Keywords: Heavy metals,Soil pollution,Soils,Kim loại nặng,Ô nhiễm đất,Đất; Environmental aspects,Heavy metal content,Khía cạnh môi trường,Nhiễm kim loại nặng